Error Analysis of Language in Political Party Banner In Nagan Raya Regency, Aceh - Amnur Rifai Dewirsyah (Budapest International Research and Critics University, 2018)
This study aims to describe the Indonesian language errors found in writing Political Party banners in Nagan Raya City. The approach used in this study is a theoretical and methodological approach. The theoretical approach in this study uses the Indonesian language error analysis approach, while the methodological approach used is a qualitative descriptive approach. Data collection was carried out using direct observation (observation), note-taking techniques, and documentation. Analysis of the data using split and replace techniques. Presentation of the results of data analysis using informal methods. The research design carried out is: (1) The initial stage is the preparation stage to identify problems and search for literature studies especially with reference to previous research journals, (2) after the problems have been identified and the basics of literature study are found, the next stage is conducting data collection with direct observation or observation, (3) After the data has been collected, recorded and documented, then analyzed using reference sources, (4) Evaluating to obtain new data as a basis for concluding the results of the study. The conclusion from the results of this study is that there are still many errors in Indonesian language in writing banners in Nagan Raya District that are not / not in accordance with the good and correct Indonesian language rules. Forms of writing errors on Political Party banners in Nagan Raya Regency. Includes writing errors of standard words and non-standard words.